Working capital financing and corporate profitability in the ASEAN region: the role of financial development - Setianto, Rahmat Heru; Sipayung, Rani Septiani; W. N., W. Azman Saini (Cracow University of Economics, 2022)
Objective: The objective of the article is to empirically investigates the role played by financial development in determining the relationship between working capital financing and firms’ performance. Research Design & Methods: Employing data of publicly listed manufacturing firms in five ASEAN countries, namely, Indonesia, Malaysia, Philippines, Singapore, and Thailand spanning from 2009-2018 resulted in 6,183 firm years observation. This study conducts an analysis using the two-steps generalized method of moments (GMM) estimator. Findings: The inverted U-shape effect of working capital financing on firm profitability is confirmed, indicating a trade off in utilizing short-term debt to finance working capital requirements. Moreover, new evidence was shown that firms which operate in more financially developed regions have the opportunity to utilise a greater percentage of short-term debt without destroying their profitability.